IMPLIKASI METODE SYAWIR DAN METODE LEARNING TOGETHER TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA SMP ALBERR PANDAAN - Imron hamzah, Mohammad; Muhammad Nur Hadi; M Anang Sholikhudin; Muhammada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the continued dominance of the lecture method in teaching, which results in low student participation, motivation, and academic achievement. Therefore, there is a need for more active and collaborative teaching methods. The syawir method, as a consensus-based approach, and the learning together method, as a cooperative learning model, are considered capable of increasing student engagement in the learning process. The objective of this study is to determine the effect of the syawir method and the learning together method on improving the academic achievement of students at SMP ALBERR Pandaan, both partially and simultaneously. This study employs a quantitative approach using an experimental design. The study sample consisted of 126 students selected using proportional random sampling. Data collection was conducted via a Likert-scale questionnaire that had been validated for both validity and reliability. Data analysis techniques included linearity tests, t-tests, and F-tests via multiple linear regression. The results showed that, partially, the Syawir method had a positive and significant effect on academic achievement with a t-value of 8.556 and a significance level of 0.000 (<0.05). The learning together method also had a positive and significant effect with a t-value of 7.326 and a significance level of 0.000 (<0.05). Simultaneously, both methods showed a significant effect on academic achievement with an F-value of 79.265 and a significance level of 0.000 (<0.05). Thus, the combination of the syawir method and collaborative learning is effective in improving student academic performance.